The association of the age, period, and birth cohort with 15-year changes in body mass index and waist circumference in adults: Tehran lipid and glucose study (TLGS) - Maryam Barzin; Shayan Aryannezhad; Mohammad Bagheri; Maryam Mahdavi; Majid Valizadeh; Fereidoun Azizi; Farhad Hosseinpanah (BMC, 2022)
Abstract Objective To examine the association of age, period, and birth cohort with body mass index (BMI) and waist circumference (WC) changes among the participants of the Tehran Lipid and Glucose Study from 1999 to 2015. Methods This prospective cohort study included 4895 participants aged ≥20 years (41.3% men), who were divided into twelve gender stratified groups, having a ten-year age difference between them. Analyses were conducted to explicitly assess the association of age vs. period on BMI and WC changes. In addition, we evaluated BMI and WC changes among different birth cohorts. Results Upon 15 years of follow-up, the mean BMI of men and women increased from 26.0 ± 3.9 to 27.5 ± 4.3 kg/m2 and from 27.5 ± 4.8 to 29.9 ± 5.4 kg/m2 (P trend < 0.001), and this trend was accompanied by an increase in WC from 88.8 ± 10.9 to 97.8 ± 10.4 cm and from 87.3 ± 12.4 to 95.8 ± 12.1 cm, respectively (P trend < 0.001). Men and women in all age cohorts tended to have a rise in their BMI and WC with aging throughout the follow-up period. For men, this trend was more prominent in younger birth cohorts at phase III for BMI and at phases III and V for WC (indicating a significant negative association with birth cohort). For women, this trend was more prominent in older birth cohorts at both phases III and V for BMI and WC (indicating a significant positive association with the birth cohort). Conclusion The rise in BMI and WC was strongly associated with age in both sexes. The men born in the recent birth cohorts and the women born in earlier birth cohorts had the most alarming BMI and WC trends. More efforts must be spent on obesity prevention policies, especially for younger men.